Effect of Porosity on Structure, Young's Modulus, and Thermal Conductivity of SiC Foams by Direct Foaming and Gelcasting. Issue 1 (6th October 2016) - Jana, Dulal Chandra; Sundararajan, Govindan; Chattopadhyay, Kamanio
Abstract : The study demonstrates the aqueous processing of solid‐state‐sintered SiC foams by gelcasting technique. Aside from increasing strength of green bodies, gelcasting monomers were the source of carbon additive which helped in sintering of SiC foams. Sintered foams with the relative density (RD) between 0.44 and 0.11 were processed by direct foaming of SiC slurries followed by gelcasting and sintering. Structural analysis by X‐ray tomography showed the presence of spherical pores with bimodal pore size distribution and the proportion of large size cell and their interconnectivity increased in low RD foams. SEM study revealed that decreased RD resulted in gradual changes in the strut microstructure from the grains with faceted interface to smooth interfaced grains. The analysis of changes in Young's modulus and thermal conductivity with RD were in agreement with the Ashby model for open cell foams.